2020
DOI: 10.1177/0269881120913152
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine use – has practice changed?

Abstract: Background: One-third of individuals with schizophrenia have treatment-resistant illness. Of these, up to 60% will respond to clozapine treatment. Aims: This study retrospectively examined clozapine prescribing patterns against National Institute for Health and Care Excellence (NICE) guidelines as treatment-resistant illness emerged in a first-episode psychosis cohort. Methods: A total of 339 individuals with a first-episode psychosis were included in the study. Clozapine prescribing patterns were compared aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…No other published studies within the identified underprioritized areas were found. Instead, eight additional studies on general clinician perspectives on clozapine treatment [203][204][205][206][207][208][209][210] , three additional studies on clozapinepatients' (and their clinicians') attitudes towards their ongoing treatment 40 211 212 , and three additional studies on case-note derived reasons for clozapine cessation or withholding [213][214][215] appeared, ratifying the repetitive behavior of current research and the importance of disseminating these results in order to direct future research towards more meaningful and less well-described areas.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…No other published studies within the identified underprioritized areas were found. Instead, eight additional studies on general clinician perspectives on clozapine treatment [203][204][205][206][207][208][209][210] , three additional studies on clozapinepatients' (and their clinicians') attitudes towards their ongoing treatment 40 211 212 , and three additional studies on case-note derived reasons for clozapine cessation or withholding [213][214][215] appeared, ratifying the repetitive behavior of current research and the importance of disseminating these results in order to direct future research towards more meaningful and less well-described areas.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…At present, clozapine remains the standard treatment of choice for TRS recommended by international guidelines due to its superior efficacy compared to other existing antipsychotics [3][4][5][6][7]. Despite the abundance of robust evidence supporting the effectiveness of clozapine in improving outcomes for TRS patients, clozapine is underutilized due to concerns about tolerability and monitoring [8], and its initiation is commonly delayed for several years in many countries worldwide, including in the USA and Canada [9][10][11]. Studies have even suggested that the utilization of clozapine earlier in treatment, rather than waiting for multiple drug failures and subsequent severe TRS, results in better response [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the real-world data indicate that patients who discontinued LAI antipsychotics eventually needed to resume LAI antipsychotics or receive antipsychotic polypharmacy, which indicates that earlier use of clozapine may be useful. 6…”
mentioning
confidence: 99%